NEUTROPHIL LYMPHOCYTE RATIO IN PATIENTS WITH MAJOR DEPRESSIVE DISORDER - Korkmaz, Sevda; Denk, Affan; Gundogan, Burcu; Korucu, Tuba; Dulkadir, Zehra Emine; Telo, Selda; Atmaca, Murad (Carbone Editore, 2016)
Introduction: Neutrophil - lymphocyte ratio (NLR) is accepted as an inflammation marker. The objective of the study is to indicate the variations in NLR that occur in patients with major depressive disorder. Materials and methods: Forty prospective patients diagnosed with major depressive disorder based on DSM 4-TR and treated in our clinic were included in the study. The control group included forty healthy individuals that applied to our clinic, however were not diagnosed with active psychopathology in the initial examination, and have matching age and gender demographics with the patient group. Lymphocyte and neutrophil percentages taken during the application before the treatment were recorded in the related forms. NLR was calculated by the division of neutrophil rate by the lymphocyte rate for each patient. Results: There was no significant difference between the groups based on socio-demographic characteristics such as age, gender, marital status, income level, smoking, and employment. Mean NLR value was 1.58 +/- 0.59 in the patient group, and it was 2.05 +/- 0.89 in the control group. The difference between these mean values was statistically significant (p=0.007). In control group, the neutrophil percentage, and in patient group the lymphocyte percentage was significantly high. There was no difference between the groups on white blood cell count. Conclusion: It was determined that the NLR is significantly lower in patients with major depressive disorder when compared to the control group. The changes in NLR could reflect the changes in central nervous system metabolisms. Thus, NLR could be an indicator of the fact that immune system is suppressed in chronic inflammation in psychiatric diseases such as depressive disorder.
Keywords: Neutrophil; lymphocyte; major depressive disorder; inflammation